Implementation and organization of the circle of research and development of software and automation - CIDESOFT - Lorena L., Paul (2002)
Currently the area of computing is in permanent crisis, continuous change, and the emergence of new and emerging technologies in the management of information has become a constant, today the competitiveness of a company and a government begins quantified according to the efficiency that handles and manages its information. In Peru, SMEs absorb 60% of the economically active population, account for about 96% of all businesses and contribute, along with the mid-market, with 40% of production nacional1.